SOSIALISASI PENTINGNYA GERMAS DALAM MENINGKATKAN KESEHATAN LINGKUNGAN - apriyani, Apriyani; Kusumawati, Rindha Mareta; Suwignyo; Wulandari, Kartina (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2025)
This research focuses on the implementation of the Healthy Living Community Movement (Germas) in the Pulau Atas Subdistrict community of Samarinda City. Germas represents a systematic and planned collective effort aimed at enhancing the quality of life by promoting healthy behaviors. Using a quantitative descriptive research design and incidental sampling techniques for respondent selection, the study is scheduled for May 2023. The study primarily addresses Germas's role in fostering a healthier environment, encompassing waste management, water quality, and sanitation. Through community surveys and observations, the research aims to assess Germas practices and awareness, identifying implementation challenges and opportunities. The research output is expected to yield valuable insights into the effectiveness of Germas initiatives in promoting a healthier environment. Data collection involves surveys and observations within the Pulau Atas Subdistrict community, with subsequent analysis to gauge Germas awareness and implementation levels among residents. The findings will illuminate the current status of Germas in the community, emphasizing areas for improvement and potential interventions. In conclusion, this research enhances Germas understanding and promotes a healthier environment by evaluating practices and awareness, providing recommendations for Pulau Atas Subdistrict, Samarinda City